Genocidas ir rezistencija Nr. 3(1) - Banionis, Juozas; Anušauskas, Arvydas; Starkauskas, Juozas; Kasparas, Kęstutis; Grybkauskas, Saulius; Bubnys, Arūnas; Pocius, Mindaugas; Truska, Liudas (Genocidas ir rezistencija, 1998)
Pilnas leidinys (nuskenuota popierinė versija)